C.O.W.L. Volume 1, Principles of power - Higgins, Kyle, 1985-; Siegel, Alec (Image Comics, 2014)
"The Chicago Organized Workers League once stood as a beacon of hope against an epidemic of organized crime and an unbeatable "brotherhood" of Super-Villains. Now, in 1962, the union faces a disillusioned public, scandal, and a new era of threats" --